115. Post-licensure Safety Study of New-onset Immune-mediated Diseases, Herpes Zoster, and Anaphylaxis in Adult Recipients of HepB-CPG Vaccine Versus HepB-alum Vaccine. (15th December 2022) - Ackerson, Bradley; Sy, Lina S; Slezak, Jeff; Qian, Lei; Reynolds, Kristi; Huang, Runxin; Solano, Zendi; Towner, William; Qiu, Sijia; Simmons, Sarah; Jacobsen, Steven; Bruxvoort, Katia J
Abstract: Background: HepB-CpG (Heplisav-B; Dynavax) is a licensed hepatitis B vaccine with a novel adjuvant that requires only 2 doses (0, 1 month) compared to a 3-dose (0, 1, 6 months) HepB-alum vaccine (Engerix-B; GlaxoSmithKline). Monitoring of safety outcomes following receipt of vaccines with novel adjuvants is important. Hence, as part of an FDA postmarketing commitment, we compared the incidence of new-onset immune-mediated diseases, herpes zoster (HZ), and anaphylaxis among recipients of HepB-CpG versus HepB-alum at Kaiser Permanente Southern California (KPSC). Methods: This cohort study included adults not on dialysis who received ≥1 dose of a hepatitis B vaccine from 8/7/2018 to 10/31/2019, during which HepB-CpG was routinely administered in 7 of 15 KPSC medical centers while HepB-alum was administered at the other 8 medical centers. Recipients of HepB-CpG or HepB-alum were followed through electronic health records for 13 months after receipt of the first dose during the vaccine accrual period for occurrence of pre-specified new-onset immune-mediated diseases, HZ, and anaphylaxis identified using diagnosis codes. Incidence rates were compared using Poisson regression with inverse probability of treatment weighting when there was 80% power to detect a relative risk (RR) of 5 for anaphylaxis and a RR of 3 for all other outcomes Results: There were 31, 183 HepB-CpG and 38, 442 HepB-alum recipients (overall 49.0% female, 48.5% ≥50 years of age, and 49.6% Hispanic). Among immune-mediated events that occurred frequently enough for formal comparison, rates among HepB-CpG versus Hep-B-alum recipients were similar except for rheumatoid arthritis (RA) (adjusted RR 1.53 [95% CI: 1.07, 2.18]). (Table 1) After adjudication of new-onset RA, the adjusted RR was 0.93 (0.34, 2.49). (Table 2) The adjusted RR for HZ was 1.06 (0.89, 1.27). Anaphylaxis occurred in 0 HepB-CpG and 2 HepB-alum recipients. Conclusion: These data suggest no safety concerns for HepB-CpG compared to HepB-alum for select immune-mediated diseases, HZ, or anaphylaxis in this observational study of over 69, 000 recipients of hepatitis B vaccines. Disclosures: Bradley Ackerson, MD, Dynavax: Grant/Research Support|Glaxosmithkline: Grant/Research Support|Moderna: Grant/Research Support|Pfizer: Grant/Research Support|Seqirus: Grant/Research Support Lina S. Sy, MPH, Dynavax: Grant/Research Support|Glaxosmithkline: Grant/Research Support|Moderna: Grant/Research Support|Seqirus: Grant/Research Support Jeff Slezak, MS, ALK, Inc.: Grant/Research Support|Dynavax: Grant/Research Support|Novavax, Inc.: Grant/Research Support|Pfizer, Inc.: Grant/Research Support Lei Qian, PhD, Dynavax: Grant/Research Support|Glaxosmithkline: Grant/Research Support|Moderna: Grant/Research Support Kristi Reynolds, PhD, Amgen: Grant/Research Support|Dynavax: Grant/Research Support|Merck: Grant/Research Support|Novartis: Grant/Research Support Runxin Huang, MS, Dynavax: Grant/Research Support Zendi Solano, BS, Dynavax: Grant/Research Support|Gilead: Grant/Research Support|GlaxoSmithKline: Grant/Research Support William Towner, MD, Dynavax: Grant/Research Support|Gilead: Grant/Research Support|Merck: Grant/Research Support|Moderna: Grant/Research Support|Pfizer: Grant/Research Support|ViiV: Grant/Research Support Sijia Qiu, MS, Dynavax: Grant/Research Support|Moderna: Grant/Research Support Sarah Simmons, MPH, Dynavax: Grant/Research Support|Glaxo-Smith Kline: Grant/Research Support|Pfizer: Grant/Research Support Steven Jacobsen, MD, Dynavax: Grant/Research Support Katia J. Bruxvoort, PhD, MPH, Dynavax: Grant/Research Support|Gilead: Grant/Research Support|Glaxosmithkline: Grant/Research Support|Moderna: Grant/Research Support|Pfizer: Grant/Research Support|Seqirus: Grant/Research Support.